Nested Bi-level scheduling strategy for energy storage systems in hybrid microgrid considering uncertainties of battery dynamic performances - Jiazhi Lei; Zhao Liu (International Journal of Electrical Power & Energy Systems)
This paper proposed a nested bi-Level scheduling strategy for energy storage systems in hybrid microgrid considering uncertainties of battery dynamic performances. Firstly, the uncertainties in dynamic performances caused by fitting error including efficiencies, self-discharge rate, cycle life and capacity fading were modeled by interval method and probability distribution method. Simultaneously, the significant influences of battery dynamic performances on power outputs of battery were specially quantized by direct physical influence, direct electric quantity influence and indirect state influence. Then, a nested bi-level optimization model was developed for specifying the scheduling strategy of energy storage systems. Inner layer optimization was applied for realizing the operation strategy optimization of battery ESSs and outer layer optimization was applied for realizing the battery performance optimization. Case studies based on multi-scene generation mode verified the effectiveness of the proposed nested bi-level scheduling strategy. With the increase of battery dynamic performances uncertainties, more economic benefits are brought by energy storage battery, but the battery dynamic performances continuously decline. Compared with single layer optimization, nested bi-level optimization scheduling model slightly reduced the total benefits, but the battery dynamic performances f1 is significantly improved by about 20%.